2001
DOI: 10.1159/000049109
|View full text |Cite
|
Sign up to set email alerts
|

CaF<sub>2</sub> Formation: Cariostatic Properties and Factors of Enhancing the Effect

Abstract: CaF2 or a CaF2-like material/phosphate-contaminated CaF2 is a major reaction product during topical treatment of dental hard tissues. Recently, evidence has suggested that CaF2 is formed not only on surfaces but also to some extent in the enamel. The minimum concentration of fluoride required for CaF2 formation is not well known and may depend on whether calcium is available from plaque fluid or only through dissolution of the dental hard tissue. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
27

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 19 publications
1
83
0
27
Order By: Relevance
“…The acidic ZnF 2/HCl solution would be neutralized when applied to the dentin surface. Thus, ZnF2/HCl was expected to produce precipitations of Zn 2+ -containing compounds, such as phosphate and fluoride, and CaF2-like materials 26) . These compounds are inherently less soluble at a range of neutral pH, providing a reservoir for zinc and fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…The acidic ZnF 2/HCl solution would be neutralized when applied to the dentin surface. Thus, ZnF2/HCl was expected to produce precipitations of Zn 2+ -containing compounds, such as phosphate and fluoride, and CaF2-like materials 26) . These compounds are inherently less soluble at a range of neutral pH, providing a reservoir for zinc and fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…However, the decrease in CaF 2 formation could interfere in inhibition of the dynamic of caries process, due to its capacity to act as a pH-controlled reservoir of ions on enamel and dental plaque that can be released during cariogenic challenges. 17,18) …”
Section: Discussionmentioning
confidence: 99%
“…Two different types of F -uptake have been shown to occur on the surface of enamel: firmly-bound and loosely-bound F -(as CaF 2 ) 10) . CaF 2 can work as a reservoir of F -in enamel and support remineralization of firmly-bound F -because CaF 2 shows higher solubility and provides F -at a neutral or lower pH 26) . Recently, it has been revealed that CaF 2 nanoparticles are also eff ective at suppressing formation of Streptococcus mutans biofi lms 27) .…”
mentioning
confidence: 99%